FORMALIZATION OF TASKS TO ENSURE THE SAFETY OF EMERGENCY AND EXPLOSIVE OPERATIONS IN THE MINING INDUSTRY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The development of quarries and underground mines is characterized by the need to expand their borders and resume the work of temporarily non-working sections of the countries, as well as maintain the capacity for ore production, the reduction of which is associated with a reduction in the active area of ore bodies. At the same time, work intensification is necessary, which is complicated by the limited size of the working area. Such complications can be largely compensated for by increasing the height of the exploding sill. At the same time, work intensification is necessary, which is complicated by the limited size of the working area. Such complications can be largely compensated for by increasing the height of the exploding sill. This is precisely the purpose of the present research, which was carried out by processing arrays of information that allows us to optimize this process. The study was carried out with machine processing of the information and change of the studied parameters.